MENINGKATKAN HASIL BELAJAR MERODA SENAM LANTAI MELALUI PENGGUNAAN ALAT BANTU PEMBELAJARAN - Achwan Susanto; Rony Syaifullah (PJKR FKOR UNS, 2018)
The purpose of this research is to improve learning outcomes of basic locomotor movements of walking and running through the medium of learning in class V SDLB Erha Pabelan Semarang 2017/2018.This research is a classroom action research. This study was conducted in two cycles, each cycle consisting of two meetings. Subjects in this Class Action Research is a fifth grade students SDLB Erha Pabelan Semarang totaling 7 students consisted of five boys and two student daughters. Sources of data in this study come from students, researchers and teachers who act as collaborators.Data collection technique used tests and observation. The validity of the data using the technique of triangulation data. Analysis of data using qualitative descriptive technique that is based on a qualitative analysis of the percentage. Results of research on pre-cycle only two students who completed (28.57%) and 5 students are not completed (71.42%). In the first cycle of learning basic movements locomotor result students who have completed as many as four students (56.67%) and 3 students are not completed (42.85%). With the acquisition of affective (57.14%), psychomotor (57.14%) and cognitive (71.42%). In the second cycle was obtained in student learning outcomes that have been completed by 6 students (85.71%) and 1 student is not completed (14.28%). With the acquisition of affective (85.71%), psychomotor (80%) and cognitive (76.67%) Based on the analysis of the first cycle and the second cycle showed an increase in the targeted achievement. Based on the results obtained the conclusion that: The use of the application of instructional media can improve learning outcomes basic motion forehand push in table tennis in Class V SDLB Erha Pabelan Semarang academic year 2017/2018.